2012
DOI: 10.1109/tro.2011.2172699
|View full text |Cite
|
Sign up to set email alerts
|

Graph-Based Observability Analysis of Bearing-Only Cooperative Localization

Abstract: In this paper we investigate the nonlinear observability properties of bearing-only cooperative localization. We establish a link between observability and a graph representing measurements and communication between the robots. It is shown that graph theoretic properties like the connectivity and the existence of a path between two nodes can be used to explain the observability of the system. We obtain the maximum rank of the observability matrix without global information and derive conditions under which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…The idea of using landmarks to aid in localization has been addressed previously in [14], [16]. There are also a number of techniques that use so-called proxy landmarks arXiv:1802.07652v2 [math.OC] 10 Jul 2018…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of using landmarks to aid in localization has been addressed previously in [14], [16]. There are also a number of techniques that use so-called proxy landmarks arXiv:1802.07652v2 [math.OC] 10 Jul 2018…”
Section: A Related Workmentioning
confidence: 99%
“…If the system is observable and linear, a bound on the uncertainty in the estimation error can be related to the the eigenvalues of the observability grammian [15]. For the problem of localization of UVs, authors in [14] have shown that each UV requires bearing measurements from two distinct landmarks for observability of the system; the observability of the system is shown using Lie derivative theory. An important problem that arises in this context is that of landmark placement, i.e., given a route for the UV, to place landmarks so that the system is always observable; this would in turn ensure the error in state estimates of the position and heading of the UV, obtained using the estimation algorithms, remain bounded [15].…”
Section: Introductionmentioning
confidence: 99%
“…rank(O)=n), a mobile robot can estimates its own state from the mea surements. Several robot researchers have utilized this analysis method [1] [2] [3], and we also employed the non linear observability matrix in our research.…”
Section: Observability Analysismentioning
confidence: 99%
“…They showed that unobservable measurements were misunder stood as observable due to linearization errors. R. Sharma et al [3] determined the maximum rank in a coopera tive localization problem and verified that robots require a minimum of two known landmarks to estimate their over all state.…”
Section: Introductionmentioning
confidence: 99%
“…However, they only studied the observability properties of two robots, and the collaborative localization problem was resolved with respect to a relative reference, i.e., the pose of the second vehicle was estimated with respect to the first vehicle. An inspiring work focusing on the observability analysis of bearing-only collaborative localization system is found in [19]. They derived the maximum rank of the observability matrix without global information and show that to achieve full observability, all nodes must connect to at least two external infrastructures with known location.…”
Section: Introductionmentioning
confidence: 99%